Electrochemical conversion of CO2 to value-added chemicals over bimetallic Pd-based nanostructures: Recent progress and emerging trends - Dang Le Tri Nguyen; Nguyen, Tung M.; Lee, Si Young; Kim, Jiwon; Kim, Soo Young; Quyet Van Le; Varma, Rajender S.; Hwang, Yun Jeong (ACADEMIC PRESS INC ELSEVIER SCIENCE, 2022)
Electrochemical conversion of CO2 to fuels and chemicals as a sustainable solution for waste transformation has garnered tremendous interest to combat the fervent issue of the prevailing high atmospheric CO2 concentration while contributing to the generation of sustainable energy. Monometallic palladium (Pd) has been shown promising in electrochemical CO2 reduction, producing formate or CO depending on applied potentials. Recently, bimetallic Pd-based materials strived to fine-tune the binding affinity of key intermediates is a prominent strategy for the desired product formation from CO2 reduction. Herein, the recent emerging trends on bimetallic Pd-based electrocatalysts are reviewed, including fundamentals of CO2 & nbsp;electroreduction and material engineering of bimetallic Pd-electrocatalysts categorized by primary products. Modern analytical techniques on these novel electrocatalysts are also thoroughly studied to get insights into reaction mechanisms. Lastly, we deliberate over the challenges and prospects for Pd-based catalysts for electrochemical CO2 conversion.